Increased activity of sugarcane sucrose‐phosphate synthase in transgenic tomato in response to N‐terminal truncation - Siti Nurul Afidah; Inyana Dwi Agustien; Parawita Dewanti; Bambang Sugiharto (Indonesian Journal of Biotechnology, 2022)
Sucrose‐phosphate synthase (SPS) is a key enzyme catalyzing the formation of sucrose‐6‐phosphate through the transfer of uridine‐diphosphate glucose (UDP‐G) as a donor to fructose‐6‐phosphate (F6P) as an acceptor. Plant SPS consists of three main domains: N‐terminal, glycosyltransferase, and C‐terminal domains. Among these, the N‐terminal domain is involved in regulating the allosteric activator glucose‐6‐phosphate (G6P). This study was directed toward determining the regulation and characterization of N‐terminal truncated SPS in transgenic tomato. In this study, the N‐terminal truncated mutant of sugarcane SPS (ΔN‐SoSPS1) and full‐length sugarcane SPS (FL‐SoSPS1) were expressed into tomato plants to verify the functional role and importance of the N‐terminal domain in plant SPS. Overexpression of ΔN‐SoSPS1 led to an up to 3‐fold increase in the specific activity of SPS compared to non‐transformant plants (WT), while the specific activity of ΔN‐SoSPS1 was higher than FL‐SoSPS1 in transgenic tomato plants. Unlike WT and FL‐SoSPS1, the ΔN‐SoSPS1 mutant was not allosterically regulated by G6P. These results indicated that deletion of the N‐terminal domain promotes the loss of allosteric activation by G6P and increases binding affinity between enzyme and substrate.